Strengthening Problem-Solving, Creativity, Collaboration, And Communication (4c) Skills In 21st Century Learning In Digital Era - Devi, Lathifah Sandra; Prasetiyo, Dwi Agung; Zakaria, Rizki Fauzi (Wiyatamandala, 2026)
The development of digital technology in the 21st century has brought significant changes in the field of education, particularly in the development of skills that are relevant to the demands of the era. One of the important skills that needs to be developed is 21st-century skills, known by the concept of the 4Cs, namely critical thinking or problem solving, creativity, collaboration, and communication. This study aims to examine the strengthening of the 4C skills in 21st-century learning in the digital era. The research uses a qualitative approach with a literature review method that analyzes various scientific articles from 2020–2025 obtained through databases such as Google Scholar, ERIC, ScienceDirect, and arXiv. The results of the study show that the 4C skills are the main competencies that must be developed in the learning process to prepare students to face global challenges and technological developments. Strengthening these skills can be carried out through the implementation of innovative learning models such as project-based learning, collaborative learning, as well as the utilization of digital technology that supports interactive, creative, and problem-solving-based learning activities. However, the implementation of 4C skills still faces several challenges, such as the dominance of conventional learning methods, limited teacher understanding of 21st-century learning strategies, and the lack of technological facilities in some educational institutions. Therefore, it is necessary to improve teacher competence, provide educational policy support, and optimize the use of digital technology so that learning can effectively develop 21st-century skills.